FTO is a transcriptional repressor to auto-regulate its own gene and potentially associated with homeostasis of body weight. (16th May 2018) - Liu, Shu-Jing; Tang, Hui-Ling; He, Qian; Lu, Ping; Fu, Tao; Xu, Xu-Ling; Su, Tao; Gao, Mei-Mei; Duan, Shumin; Luo, Yan; Long, Yue-Sheng
Abstract: Fat mass and obesity-associated (FTO) protein is a ferrous ion (Fe 2+ )/2-oxoglutarate (2-OG)-dependent demethylase preferentially catalyzing m 6 A sites in RNA. The FTO gene is highly expressed in the hypothalamus with fluctuation in response to various nutritional conditions, which is believed to be involved in the control of whole body metabolism. However, the underlying mechanism in response to different nutritional cues remains poorly understood. Here we show that ketogenic diet-derived ketone body β-hydroxybutyrate (BHB) transiently increases FTO expression in both mouse hypothalamus and cultured cells. Interestingly, the FTO protein represses Fto promoter activity, which can be offset by BHB. We then demonstrate that FTO binds to its own gene promoter, and Fe 2+, but not 2-OG, impedes this binding and increases FTO expression. The BHB-induced occupancy of the promoter by FTO influences the assembly of the basal transcriptional machinery. Importantly, a loss-of-function FTO mutant (I367F), which induces a lean phenotype in FTO I367F mice, exhibits augmented binding and elevated potency to repress the promoter. Furthermore, FTO fails to bind to its own promoter that promotes FTO expression in the hypothalamus of high-fat diet-induced obese and 48-h fasting mice, suggesting a disruption of the stable expression of this gene. Taken together, this study uncovers a new function of FTO as a Fe 2+ -sensitive transcriptional repressor dictating its own gene switch to form an auto-regulatory loop that may link with the hypothalamic control of body weight.